Nation and Cultural Branding on Instagram: Case Study of Indonesian Arts and Culture Scholarship (IACS) Campaign Program - Dewi, Ni Putu Eka Budi Pradnya Wulandari; Effendi, Nursyirwan; Chatrs, Emeraldy (CHANNEL: Jurnal Komunikasi, 2022)
Indonesian Arts and Culture Scholarship (IACS), which displays Indonesian arts, and culture, is a program that the Directorate of Public Diplomacy holds for the Ministry of Foreign Affairs of the Republic of Indonesia. This program was started in 2003 and took place face-to-face until 2019. This program becomes an excellent opportunity for Indonesia to spread Indonesian values by forming nation-branding and creating a national image through soft diplomacy. This research analyzes how Instagram can play an essential role in promoting the 2019 IACS program so that the general public can know about this program. This research was analyzed by using the Circuit of Culture model. It is specified in Production moment to disclose how Studios and MoFA distributed messages through Instagram. By analyzing Instagram, we can find out how the account is managed and the content shared by the committee that holds the Instagram account. Data were taken based on interviews, social media, and government documents. The results are that MoFA does not use Instagram @iacs_kemlu well. It can be seen from the re-confirmation absence to the public regarding the date range of its program. As well as the minimal upload of documentation of the participants, MoFA is not carrying out the monitoring function regarding the inactive @bsbi_pdg account. Besides that, on Instagram @iacs.banyuwangi, Instagram management could be better. It can be seen on its Instagram account page.